2008
DOI: 10.1007/s10461-008-9500-3
|View full text |Cite
|
Sign up to set email alerts
|

HIV Services Utilization in Los Angeles County, California

Abstract: Recipients of HIV/AIDS prevention services in Los Angeles County California were surveyed in 2004 by 220 HIV prevention service provider staff from 51 agencies funded by the Office of AIDS Programs and Policy. This resulted in 2,102 usable surveys for cluster analysis purposes. This Countywide Risk Assessment Survey assessed demographics, sexual history, substance use, perceptions regarding HIV/AIDS, and use of 18 different services at both the agency administering the survey and at other agencies. The 36 type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…One study of service utilization by more than 2,100 consumers of HIV prevention and care programs in California showed a wide-range of services accessed, with some individuals receiving multiple services and others receiving none. Similar to previous research (Lo, MacGovern, & Bradford, 2002), Fisher and colleagues (2010) found that accessing and utilizing HIV-related services was related to receiving ART.…”
supporting
confidence: 84%
“…One study of service utilization by more than 2,100 consumers of HIV prevention and care programs in California showed a wide-range of services accessed, with some individuals receiving multiple services and others receiving none. Similar to previous research (Lo, MacGovern, & Bradford, 2002), Fisher and colleagues (2010) found that accessing and utilizing HIV-related services was related to receiving ART.…”
supporting
confidence: 84%
“…The potential mediator variables included use of specific types of drugs (marijuana, opiates such as heroin and non-prescription methadone, crack, cocaine, amphetamine) in the last 30 days, use of injected drugs, and whether the respondent had ever traded sex for drugs or money. Previous work has indicated that these variables are associated with health services usage among at-risk individuals in Los Angeles County (Erlyana, et al 2014 in press) especially those who access publicly funded HIV and sexually transmitted diseases testing services (Fisher, et al 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Stratified sampling was employed because it was believed that there were differences in client characteristics among the different agencies. Systematic sampling was used to facilitate a representative sample of participants (Fisher, et al, 2010). Each interviewer was given a number (n) after he/she completed six hours of training on the CRAS and was told to interview each nth client.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were offered one of three incentives for completing the CRAS: 1) a non cash food voucher worth $10; 2) two movie tickets with an approximate value of $20; or a non cash gift card in the amount of $15. The data collection methods used for the CRAS have been previously described in detail (Edwards, Fisher, & Reynolds, 2007; Fisher, et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation